Impact of competence development, on work creativity, employee performance, and competitiveness of woven products - Ida Ayu Oka Martini; A. A. N. Eddy Supriyadinata Gorda; A. A. N. Oka Suryadinatha Gorda; Desak Made Febri Purnama Sari; Made Ermawan Yoga Antara (Cogent Business & Management, 2024)
This study was conducted to analyze the role of work competence on work creativity, employee performance, and the competitiveness of woven products produced by SMEs. The research population is weaving employees in 152 weaving companies in Bali. The research sample was determined using the Slovin formula with a precision of 7%, so the total sample was 187 respondents spread over seven districts/cities in Bali. The process of collecting research data is done by distributing questionnaires to respondents, and then the collected data was analyzed using the SmartPLS 3.0 program. The results of the analysis show that competence has a significant positive effect on work creativity, employee performance, and product competitiveness. Work creativity also has a significant positive effect on employee performance. Employee performance shows a significant positive effect on product competitiveness. Work creativity and employee performance separately and together act as a mediation on the relationship between competence and product competitiveness.Woven products in Bali are well known locally, and even internationally. This cloth is traditionally worked on. The work results of the workers have not been optimal, given the limited competency they have because they have never received education/training related to weaving work. In terms of work competence (knowledge, skill, and attitude) are needed to support the performance of workers.
Keywords: 650; Competitiveness; performance; creativity; competence; Bali